A novel approach to London: Infusing ethnography and the study abroad experience. Issue 2 (3rd April 2017) - Schaefer, Zachary A.; Lynch, Owen H.
Abstract : Courses: Qualitative Research Methods, Ethnographic Research Methods. Objective: This purpose of this activity is to document the enculturation process through which students begin to understand a new culture during a study abroad experience. To accomplish this, we created a new pedagogical approach for study abroad experiences that involved a combination of academic and fictional readings to help students make sense of and perform ethnographic research techniques.